Protective effect of 940 nm laser on gamma-irradiated mice - Efremova, Yulia; Sinkorova, Zuzana; Navratil, Leos (Photomedicine and laser surgery, 2015)
OBJECTIVE: The purpose of this study was to investigate the radioprotective features of 940 nm laser on the life span of mice, and absolute counts of blood cells and their proportions in gamma-irradiated mice. BACKGROUND DATA: An important feature of laser light is activation of mitotic division and differentiation of cells, which may be useful in activation of hematopoiesis in gamma-irradiated organisms. MATERIALS AND METHODS: Mice were randomly assigned to 11 groups according to the type(s) of influence. Generally, mice were irradiated in three different ways: with laser at different fluences, with gamma irradiation, or by combination of laser at different fluences and gamma irradiation in a different order. Mice were treated with 940 nm laser at 3, 12, or 18 J/cm(2) and/or a lethal dose of gamma irradiation (8.7 Gy). Each group was randomly subdivided into two subgroups, in which the life span of the mice and blood cell counts (on 12th and 45th day after gamma irradiation) were analyzed. RESULTS: Laser (940 nm) at a fluence of 3 J/cm(2) significantly prolonged the life span of gamma-irradiated mice (p<0.05). In the same group, counts of white blood cells, lymphocytes, and neutrophils were higher on day 12 than in the gamma group. On day 45 after gamma irradiation, some signs of hematopoiesis repair were found in blood. There were no significant differences in counts of erythrocytes, monocytes, neutrophils, or the proportion of neutrophils between this group and the control group. CONCLUSIONS: In summary, 940 nm laser at a fluence of 3 J/cm(2) demonstrates radioprotective features in an experiment with lethally irradiated mice. Mechanisms responsible for this effect will be investigated in further studies.
Keywords: Random Allocation; laserová terapie s nízkou intenzitou světla; lasery polovodičové; krevní obraz; myši inbrední C57BL; Lasers, Semiconductor; dlouhověkost; Mice; záření gama; Longevity; Blood Cell Count; ženské pohlaví; zvířata; náhodné rozdělení; myši; Low-Level Light Therapy; Female; Mice, Inbred C57BL; Gamma Rays; Animals